Studi Fitokimia Dan Farmakologi Buah Pisang Kayu (Musa Paradisiaca L. Var. Kayu) Sebagai Antidiare - Wulandari, Winda; Klau, Ivan Charles S.; Nurmalasari, Devy Artanti; Santyas, Aisyah Adellina; Zahra, Maulidya Rachma Az; Maharani, Tiara Anisa; Sofia, Armelia Idawati; Parnaen, Shawa Satria; Ningsih, Arista Wahyu (LPPM-KI - POLTEKKES PIM (Formerly AKAFARMA-AKFAR PIM, 2025)
Banana kayu is a fruit that contains phenolics. Phenolic compounds have pharmacological effects as antidiarrheal agents. Objective: This article review aims to identify the chemicals present in the banana kayu plant (Musa paradisiaca L. Var. Kayu) and examine its pharmacological effects. Method: The employed methodology is the literature search technique. Results: This journal review article examines the pharmacological activity of banana kayu, namely antidiarrheal, antibacterial, antimicrobial, antiviral, anti-inflammatory, astringent, and antioxidant properties in various portions of the banana kayu. Banana kayu comprises components including alkaloids, tannins, saponins, flavonoids, steroids, and serotonin. Conclusion: Multiple assessments indicate that the fruit of the banana kayu plant possesses diverse compounds with numerous benefits.